Analysis of Capital Structure's Impact on Financial Performance in Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the Years 2017-2021 - Muhammad As'adi; Fanlia Prima Jaya; Muhammad Nurdin (Hut Publication Business and Management, 2024)
This study aims to understand the Analysis of Capital Structure on Financial Performance. The independent variable (X) examined is Capital Structure (X), with the dependent variable (Y) being Financial Performance (Y). Several previous studies on company value have shown varying results. Therefore, further research is needed to retest the theory regarding financial performance. The population used in this study consists of Property and Real Estate Companies Listed on the Indonesia Stock Exchange from 2017 to 2021. Sample selection utilized purposive sampling techniques, resulting in a sample size of 20 samples. The data analysis technique employed in this research is simple linear regression analysis. Hypothesis testing is done using the coefficient of determination and partial (t) tests. Based on the test results, it can be concluded that financial performance does not have a significant impact on financial performance in Property and Real Estate Companies Listed on the Indonesia Stock Exchange from 2017 to 2021. According to the research findings, the researcher suggests that companies continue to enhance and improve financial performance to enhance the company's ability to generate profit and attract investor attention. Advice for investors is to carefully consider a company's performance level and other influencing factors on financial performance before deciding to invest capital. For future researchers, it is recommended to include other variables that influence company value, extend the research period, or incorporate more recent data. Additionally, for the government, a high-interest rate leads to reduced consumer property purchases, causing a decline in demand and property prices. Hence, government intervention is necessary to lower interest rates and boost consumer purchasing power.